2015
DOI: 10.1074/jbc.m115.637439
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role for Zinc Transporter 2 (ZnT2)-mediated Zinc Transport in Mammary Gland Development and Function during Lactation

Abstract: Background: ZnT2 is expressed in non-secreting and secreting mammary epithelium; however, the physiological role is not understood. Results: ZnT2-null mice have impaired mammary expansion and compromised mammary differentiation and milk secretion during lactation. Conclusion: ZnT2-mediated zinc transport is critical for mammary development and function during lactation. Significance: This study identifies novel consequences of ZnT2 function in the mammary gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 79 publications
(84 reference statements)
5
65
0
Order By: Relevance
“…Interestingly, many women in our study carried compound substitutions in ZnT2, similar to what Itsumura and colleagues [10] recently reported in a woman with reduced milk [Zn]. Because we recently reported that ZnT2-null mice had profound defects in mammary gland function and milk secretion in general [14], our study implicates genetic variation in SLC30A2 as a modifier of mammary gland biology, which may have consequences on both maternal and infant health.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Interestingly, many women in our study carried compound substitutions in ZnT2, similar to what Itsumura and colleagues [10] recently reported in a woman with reduced milk [Zn]. Because we recently reported that ZnT2-null mice had profound defects in mammary gland function and milk secretion in general [14], our study implicates genetic variation in SLC30A2 as a modifier of mammary gland biology, which may have consequences on both maternal and infant health.…”
Section: Discussionsupporting
confidence: 85%
“…However, we recently showed that the redistribution of ZnT2 from secretory vesicles to lysosomes activates lysosomal-mediated cell death and mammary gland remodeling during involution [13]. Moreover, ZnT2-null mice have profound defects in mammary gland function, secretion and milk composition [14], implicating ZnT2-mediated Zn transport in processes that extend well-beyond Zn secretion into milk. Because appropriate Zn management is critical for modulating a vast array of biological processes including endoplasmic reticulum (ER) stress [15], intracellular signaling [16], vesicular trafficking [4] and autophagy [17], inappropriate sub-cellular Zn transport may have important implications for cell function.…”
Section: Introductionmentioning
confidence: 98%
“…ZnT2 is a key mediator of zinc transport into vesicles in mammary gland epithelial cells (2,26). It is the sole transporter, the loss of function of which was found to cause zinc-deficient breast milk and TNZD (6 -11, 27).…”
Section: Discussionmentioning
confidence: 99%
“…However, changes in ZnT4 or ZnT2 expression are not responsible; thus, the molecular underpinnings remain unknown. While ZnT2-null mice also have a substantial reduction in secretory epithelium, this results from cytoplasmic Zn accumulation, the loss of phospho-STAT5 signaling, and profound defects in mammary gland differentiation and secretion, as opposed to precious involution (21). In contrast, while ZnT4-null mice have a substantial reduction in secretory epithelium, these defects are associated with increased ZnT2 and TNF-␣ expression and precocious activation of phospho-STAT3, which is indicative of mammary gland remodeling (9,10).…”
Section: Ck8mentioning
confidence: 99%
“…Recent studies have shown that cell signaling can be affected by alterations in subcellular Zn pools (reviewed in Ref. 24), which has critical implications for mammary gland function (5,10,21,42). For example, LMO4, a member of the LIM-only class of Zn finger transcription factors, associates with gp130 (30), coactivates JAK1, the tyrosine phosphatase SHP2, and suppressor of cytokine signaling 3 (SOCS3) (30), is a positive regulator of MEC proliferation, and is critical for mammary expansion during pregnancy (46).…”
Section: Ck8mentioning
confidence: 99%